Sugarcane Cell Wall-Associated Defense Responses to Infection by Sporisorium scitamineum - Marques, João P. R.; Hoy, Jeffrey W.; Appezzato-da-Glória, Beatriz; Viveros, Andrés F. G.; Vieira, Maria L. C.; Baisakh, Niranjan (Frontiers in Plant Science, 2018)
The plant cell wall is known to be the first barrier against plant pathogens. Detailed information about sugarcane cell wall-associated defense responses to infection by the causal agent of smut, Sporisorium scitamineum, is scarce. Herein, (immuno)histochemical analysis of two smut resistant and two susceptible sugarcane cultivars was conducted to understand host cell wall structural and compositional modifications in response to fungal infection. Results showed that the fungus grew on the surface and infected the outermost bud scale of both susceptible and resistant cultivars. The present findings also supported the existence of early (24 hours after inoculation) and later (72-96 hours after inoculation) inducible histopathological responses related to the cell wall modification in resistant cultivars. Lignin and phenolic compounds accumulated during early stages of infection. Later infection response was characterized by the formation of a protective barrier layer with lignin, cellulose and arabinoxylan in the cell walls. Overall, the results provide suggest possible induction of cell wall-modified responses in smut resistant cultivars to prevent initial entry of the fungus into the meristematic tissues.